Peptide-based and small molecule PD-1 and PD-L1 pharmacological modulators in the treatment of cancer - Islam, Mohammad Kaisarul; Stanslas, Johnson (Elsevier, 2021)
Cancer immunotherapy is an option to enhance physiological defence mechanism to fight cancer, where natural substances (e.g., antigen/antibody) or small synthetic molecule can be utilized to improve and restore the immune system to stop or slacken the development of malignant cells, stop metastasis and/or help the immune response with synthetic monoclonal antibodies (mAbs) and tumour-agnostic therapy to eliminate cancer cells. Interaction between the programmed cell death ligand 1 (PD-L1) and its receptor (programmed cell death protein 1, PD-1), and cytotoxic T-lymphocyte-associated protein 4 (CTLA4) linked signalling pathways have been identified as perilous towards the body's immune mechanism in regulating the progression of cancer. It is known that certain cancers use these pathways to evade the body's defence mechanism. The immune system is capable of responding to cancer by stalling these trails with specific synthetic antibodies or immune checkpoint inhibitors, which can ultimately either stop or slow cancer cell development. Recent findings and data suggested that using such inhibitors invigorated a new approach to cancer treatment. These inhibitors usually activate the immune system to identify and eliminate cancer cells rather than attacking tumour cells directly. PD-1/PD-L1 inhibitors have already been substantiated for their efficacy in over twenty variations of cancer through different clinical trials. Studies on molecular interaction with existing PD-1/PD-L1 inhibitors that are mainly dominated by antibodies are constantly generating new ideas to develop novel inhibitors. This review has summarised information on reported and/or patented small molecules and peptides for their ability to interact with the PD-1/PD-L1 as a potential anticancer strategy.